PRAGMATIC ASPECT OF RUSSIAN LANGUAGE TEACHING IN A MEDICAL UNIVERSITY - Nurmatova F. I. (Web of Journals Publishing, 2024)
The article deals with the pragmatic aspect of teaching Russian language in the example of a medical university. The article shows that at present there are many definitions of the term “pragmatics”, but they all pointed to the fact that pragmatics is an aspect of the study of language, highlighting and investigating language units in their relation to the person or persons who create, accept and understand them. Inclusion in the world community contributes to the development of interest in the study of other foreign languages. The desire for sources of new information on their specialty, exposure to foreign-language culture in professional, scientific and humanitarian spheres contributes to the growth of interest in the Russian language, which serves the development of tolerance - an important factor in stabilizing international cooperation and communication.
Keywords: self-evaluation reading, interest of learning Russian, develop receptive skills, reviewing the text, meeting aesthetic needs, development of generalization skills, specific vocabulary; communicative competence; syntactic features of the language.